TOURIST SATISFACTION WITH HERITAGE SITE ATTRIBUTES IN THE SULTANATE OF OMAN - Malik, Mustafa; Al-Salahmi, Safa Mohammed Khalfan; Al-Kamiyani, Nasser Khamis Nasser; Al-Habsi, Ghadeer Hamood Humaid (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2020)
Tourist satisfaction, as one of the important measures of destination performance, has been widely used by destination managers to improve their service offerings and hence attract more visitors. The present study analyses the level of satisfaction the tourists have with two heritage sites namely Nizwa Fort and Bahla Fort in the Aldhkhiliyah region of the Sultanate of Oman. 162 tourists were surveyed on-site through a bi-lingual (English and Arabic) questionnaire composed of 27 statement, 25 of which were categorized in four major variables as Facilities (9 statements), Appearance and Maintenance (4 statements), Accessibility (8 statements) and Quality of Services (4 items); and 2 statements were used to check overall satisfaction of the tourists. While the respondents were overall satisfied with the two sites, they rated certain dimensions of the two heritage sites higher than the others. It is hoped that the findings will help the site managers and policymakers at the two heritage sites to focus on the visitors’ concerns and improve on those components to increase visitor satisfaction.